2022
DOI: 10.1186/s12967-022-03769-x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of health-related factors between patients diagnosed with ME/CFS and patients with a related symptom picture but no ME/CFS diagnosis: a cross-sectional exploratory study

Abstract: Background In chronic fatigue syndrome/myalgic encephalomyelitis (ME/CFS), the capacity for activity and participation is strongly limited. The disease definition is very broad, and considering the lack of evidence for best treatment, it is important to understand what is ME/CFS-specific in the biopsychosocial perspective in comparison with similar syndromes. The objective was to study the difference between those diagnosed with ME/CFS and those with similar symptoms but no ME/CFS diagnosis for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 60 publications
2
4
0
Order By: Relevance
“…Similar to our findings, a clinical-based cross-sectional study found that, compared to people with other fatiguing symptoms, people with ME/CFS had a lower index of physical role functioning and social functioning, lower energy, worse pain and poorer overall health [48]. However, they found no difference in mental components such as anxiety, emotional role limitation, and no significant differences in physical activity and work ability.…”
Section: Discussionsupporting
confidence: 88%
“…Similar to our findings, a clinical-based cross-sectional study found that, compared to people with other fatiguing symptoms, people with ME/CFS had a lower index of physical role functioning and social functioning, lower energy, worse pain and poorer overall health [48]. However, they found no difference in mental components such as anxiety, emotional role limitation, and no significant differences in physical activity and work ability.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, psychological distress commonly concurs with chronic health conditions, which may negatively impact QoL, and health related outcomes associated with anxiety and depression ( 27 29 ). Whilst an RDC is in the first instance designed to speed up cancer diagnostics, only 7% of our patients ultimately have a cancer diagnosis ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, it is worth considering that underlying anxiety and/or depressive disorders might be contributing to NSS symptoms. For instance, patients with anxiety and/or depression often report higher levels of pain intensity compared to the general population, and the remission of an underlying depression has been linked to reduced pain severity ( 27 , 36 ). Additionally, as previously mentioned, the DSM-V outlines various NSS symptoms (i.e., weight loss and fatigue), within their criteria for major depressive disorder and generalized anxiety disorder ( 10 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, diagnosis is possibly biased by comorbidities if the diagnosed fatigue‐based disease does not fully explain symptom's characteristics 9 . An imbalance of activity–recovery, persistent negative psychosocial stress, worse pain, impaired abilities to recover from physical or mental exertion, and poorer overall health have been recorded in individuals diagnosed with ME/CFS compared to those with similar symptoms but having no ME/CFS diagnosis 165 …”
Section: Clinical Features and Diagnosismentioning
confidence: 99%
“…9 An imbalance of activity-recovery, persistent negative psychosocial stress, worse pain, impaired abilities to recover from physical or mental exertion, and poorer overall health have been recorded in individuals diagnosed with ME/CFS compared to those with similar symptoms but having no ME/CFS diagnosis. 165 From a phenomenological point of view, burnout syndromes present similarities with ME/CFS, even though burnout has been historically contextualized within a psychological setting. 166 Non-resolved fatigue accumulation overlaps with many conditions, including the overtraining syndrome, whose multi-systemic nature is usually analyzed by means of endocrine markers, immune pathways, and electrophysiological evidence.…”
Section: Differential Diagnosismentioning
confidence: 99%